Aktivitas Art Therapy (Collage) berpengaruh terhadap Self-Efficacy Pasien Skizofrenia - Anugerah, Latifah Dwi; Kurnia, Rina (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Schizophrenia is a functional psychotic condition with major disturbances in thought processes and disharmony (disruption, fragmentation) between thought processes, affect/emotions, volition, and psychomotor activity accompanied by distortions of reality, particularly due to delusions and hallucinations; fragmented associations resulting in incoherence. This condition has the potential to lower self-efficacy in patients, leading to maladaptive coping. One non-pharmacological therapy that can be provided is art therapy (collage). Objectives: This study aims to determine the effect of art therapy (collage) on self-efficacy in schizophrenia patients at Dr. Radjiman Wediodiningrat Hospital. Methods: This study is a quantitative pre-experimental design (one group pretest posttest) with a sampling technique using purposive sampling of 24 samples. Self-efficacy was measured using the Indonesian version of the General Self-Efficacy Scale (GSE). Data analysis techniques used paired sample t-test comparative analysis. Results: The results showed that the distribution based on gender was dominated by male samples (66.7%), based on age it was dominated by the late adult category (41.7%), based on diagnosis it was dominated by F.20.1 samples (Hebephrenic Schizophrenia) (70.8%), based on education level, it was dominated by junior high school graduates (45.8%), based on occupation, it was dominated by working samples (91.7%), and based on marital status, it was dominated by unmarried samples (62.5%). There was an average difference between the pre-test and post-test scores of 2.79. The results of the paired sample t-test showed a Sig.2 tailed value of 0.000 (p-value<0.05), so the hypothesis was accepted. Conclusion: Art therapy (collage) activities have an effect on the self-efficacy of schizophrenia patients at Dr. Radjiman Wediodiningrat Mental Hospital. Keywords: Art therapy (collage), Self-efficacy, Schizophrenia